Financial viability for the production of gulupa (Passiflora edulis Sims) and for its exportation to the Spanish market - Cárdenas, Juan Carlos Sierra; Rodríguez, Carolina Gómez; Buendía, Edgar Emilio Sánchez; Rivera, Maribel Pinilla (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
This article establishes the financial viability for the production and export of gulupa (Passiflora edulis Sims) to the Spanish market, including environmental, technical and economic elements. Several alternatives are presented for gulupa production, the marketing process and export to Spain, based on descriptive and exploratory methods that involved the characterization, identification and situational analysis. Additionally, we analyzed the behavior of the market, the consumption habits in Spanish, imports and exports, and economic and political relations between the two countries. By this approach it was possible to find the potential of gulupa production, the costs involved in crop development and the financial benefits it obtain by the gulupa producer to export quality products that meet Spanish market demand. This financial viability is met by reaching the invested capital recovering and to cover the opportunity cost as well as recovery of the initial investment in the sixth year.